POTENSI ERIONOTA THRAX SEBAGAI AGEN PENYEBAR PATOGEN PENYEBAB PENYAKIT LAYU BAKTERI PADA TANAMAN PISANG (BLOOD DISEASE BACTERIUM) - Radix Suharjo, Edhi Martono, dan Siti Subandiyah . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
Potential of Erionota thrax to spread the causal agen of banana bacterial wilt (Blood Disease Bacterium). This study was conducted in Gerbosari, Samigaluh, Kulonprogo, Yogyakarta and in the Laboratory of Bacteriology and Entomology, Faculty of Agriculture, Gadjah Mada University, Yogyakarta during December 2002 to June 2003. The aim of this study was to find out the potency of Erionota thrax  to spread Blood Disease Bacterium the causal agent of banana blood disease in Indonesia. A field survey was conducted to record the existance of Blood Disease Bacterium in larvae and adult E. thrax. The results show that Blood Disease Bacterium was not found in the larval stage of E. thrax. In the adult of E. thrax, the pathogen was found on the legs, wings, body surface, head and head surface, but it was not found inside the body of E. thrax.